Progress in the treatment of acute fatty liver of pregnancy and management of perioperative anesthesia review - Xuewei Qin; Xuanling Chen; Lan Yao; Jing Wang; Li Lin (BMJ Publishing Group, 2023)
Acute fatty liver of pregnancy is a rare and critical disease in obstetrics, mainly characterized by liver failure, severe coagulopathy and other clinical manifestations, with rapid progression and high mortality. This article discusses the epidemic characteristics, pathogenesis, clinical manifestations, laboratory examination, clinical diagnosis and treatment of acute fatty liver during pregnancy. This paper summarizes the related contents of perioperative anesthesia in anesthesia methods, drug selection, coagulation regulation, organ protection and postpartum disease outcome.